Practical design techniques for FR4 material-based microwave hairpin filters. - Toledo, Nikholas G. (Philippine Engineering Journal)
This paper presents practical design techniques for building hairpin filters using FR4 laminates. This type of microwave microstrip filter is among the most popular low microwave frequency filters because of its compact size and ease of manufacturing. However, building the hairpin filter using FR4 laminates is very difficult to do because of the relatively poor performance of the laminate at the microwave region. The motivation to use FR4 in the low microwave frequencies is its availability and inexpensive manufacturing process. Methods and techniques were developed to address these problems of the FR4.